The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/desc.12997
|View full text |Cite
|
Sign up to set email alerts
|

The moment‐to‐moment pitch dynamics of child‐directed speech shape toddlers’ attention and learning

Abstract: Successful communication requires attention to people and the complex signals they generate. Adapting attention from one moment to the next allows speakers and listeners to produce and perceive cues in real time and to adjust their responses in ways that facilitate an efficient exchange of information (MacDonald, 2013a, 2013b). In order to break into these dynamics of communication and learn from their caregivers, young children have to process and adapt to the rich, multidimensional information embedded in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
1
33
0
Order By: Relevance
“…Future research involving pre-verbal infants and nonhuman primates could shed light on this issue. For instance, recent research suggests that toddlers already have biases to focus on similar prosodic markers in child-directed-speech and that this may be associated with better learning 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Future research involving pre-verbal infants and nonhuman primates could shed light on this issue. For instance, recent research suggests that toddlers already have biases to focus on similar prosodic markers in child-directed-speech and that this may be associated with better learning 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, research on auditory emotional words show that, in adults, shifts towards higher F0 mean and F0 variation positively affect perceptual salience of these spoken words, engaging attention, and ultimately, favoring their intelligibility (Davis et al 2017;Dupuis and Pichora-Fuller 2014;Nencheva et al 2020). Numerous studies have addressed this topic focusing on the special speech register that human caregivers use when addressing infants (hereafter infant-directed speech or IDS).…”
Section: The Human Ability To Identify and Produce Phonemes (Within Cmentioning
confidence: 88%
“…As stated in the introduction, IDS contains melodic features that make it more similar to songs compared to say adult-directed speech (ADS). The methodological decision to use IDS was made given that previous studies that used the IPLP to examine word learning in toddlers have used this type of speech register (Schmale et al, 2011 ; Newman et al, 2018 ), and because IDS has been found to increase attention and guide word learning in toddlers (Nencheva et al, 2021 ). Nevertheless, it is possible that adding a condition in which spoken sentences are produced in ADS might lead to even better accuracy during this type of learning task, and perhaps even lead to a difference in performance with the younger participants.…”
Section: Discussionmentioning
confidence: 99%